Development of industrial internet platform and its security challenges - Rongrong JIANG; Zhengqiu WENG; Tieming CHEN (Dianxin kexue)
The deep integration of the internet and traditional industries promotes the rapid development of the industrial internet.Key factors such as digitization,networking,and intelligence have made the industrial internet platform a new infrastructure project,and new technologies like identification systems,edge computing,and digital twin have emerged.Industrial internet platforms also bring new security challenges (e.g.,terminal security,control security,and business security).Starting from the current situation of industrial internet,the technological development of the industrial internet platform was sorted out,the security challenges were analyzed,the new trends of the industrial internet security were elaborated,and a framework of “ubiquitous security” for industrial internet was proposed.